Penerapan Program Projek Penguatan Profil Pelajar Pancasila sebagai Penguatan Karakter Nasionalisme (Studi Kasus di SMK Jakarta Selatan) - Setiyonugroho, Ponco; Santosa, Yusuf Budi Prasetya (CHRONOLOGIA, 2024)
The project program to strengthen the profile of Pancasila students is a form of character education contained in the Merdeka Curriculum. In contrast to character education in the 2013 Curriculum, the project to strengthen the profile of Pancasila students is that character education is presented in a more systematic and measurable manner. One of the characters that can be developed through this program is the character of nationalism, as a mandate of national education goals. Apart from that, the project program to strengthen the profile of Pancasila students must be carried out periodically by schools as formal educational institutions. This research uses a qualitative research methodology, where the research locations are several vocational high schools in Jakarta, with respondents from school stakeholders, such as deputy principals for curriculum, teachers involved in the program and program object students. The results of this research show that all schools that are research locations can implement project programs to strengthen the profile of Pancasila students. There are various obstacles and obstacles faced by schools in its implementation. This research aims to see how the project program to strengthen the profile of Pancasila students is implemented in several vocational high schools. Are there any obstacles in its implementation.